As Fortalezas do Trabalho Doméstico: mutações e permanências sócio-históricas no campo do trabalho doméstico remunerado brasileiro (1930-2020) - Perez, Thaís Mendes Magalhães (2022)
The Brazilian domestic field, the socio-historical space of the country's specific domesticity relations, is where we turn our attention in this research. We seek to characterize and investigate its lasting and temporary transformations from the perspective of the sociological analysis of paid domestic work from the 1930s, the decade that housed the first association of domestic workers in Brazil, until 2020, the landmark of the global health collapse caused by the SARS-CoV-2 virus and which has positioned domestic workers as one of the occupational groups most vulnerable to lack of employment and contamination. We observe the reenacted permanences that insist on denouncing the processes of multiple inequalities that permeate all aspects of our society stratified in colonial strategies of domination of land, peoples, exploitation of the workforce and the sexual division of labor. Some narratives of domestic workers, both collected from the domestic work literature and from interviews in the years 2018 and 2020, in the city of Fortaleza, Ceará, move us to expand our understanding of the phenomena under investigation, their differences, interlocutions and movements. From secondary statistical data published by public research institutions, we developed descriptive statistical analyzes in dialogue with historical and sociological bibliography, aiming to demonstrate some of the political, economic and social phenomena characteristic of the chosen period and their connections with the practices of domesticity and with the new and old possibilities of domestic employment.